Maternal white blood cell count cannot identify the presence of microbial invasion of the amniotic cavity or intra-amniotic inflammation in women with preterm prelabor rupture of membranes - Musilova, Ivana; Pliskova, Lenka; Gerychova, Romana; Janku, Petr; Simetka, Ondrej; Matlak, Petr; Jacobsson, Bo; Kacerovsky, Marian (PloS one, 2017)
OBJECTIVE: The main aim of this study was to determine the relationship between the maternal white blood cell (WBC) count at the time of hospital admission in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) and the presence of microbial invasion of the amniotic cavity (MIAC) and/or intra-amniotic inflammation (IAI). The second aim was to test WBC diagnostic indices with respect to the presence of MIAC and/or IAI. METHODS: Four hundred and seventy-nine women with singleton pregnancies complicated by PPROM, between February 2012 and June 2017, were included in this study. Maternal blood and amniotic fluid samples were collected at the time of admission. Maternal WBC count was assessed. Amniotic fluid interleukin-6 (IL-6) concentration was measured using a point-of-care test, and IAI was characterized by an IL-6 concentration of ≥ 745 pg/mL. MIAC was diagnosed based on a positive polymerase chain reaction result for the Ureaplasma species, Mycoplasma hominis, and/or Chlamydia trachomatis and/or for the 16S rRNA gene. RESULTS: Women with MIAC or IAI had higher WBC counts than those without (with MIAC: median, 12.8 × 109/L vs. without MIAC: median, 11.9 × 109/L; p = 0.0006; with IAI: median, 13.7 × 109/L vs. without IAI: median, 11.9 × 109/L; p < 0.0001). When the women were divided into four subgroups based on the presence of MIAC and/or IAI, the women with both MIAC and IAI had a higher WBC count than those with either IAI or MIAC alone, and those without MIAC and IAI [both MIAC and IAI: median, 14.0 × 109/L; IAI alone: 12.1 × 109/L (p = 0.03); MIAC alone: 12.1 × 109/L (p = 0.0001); and without MIAC and IAI: median, 11.8 × 109/L (p < 0.0001)]. No differences in the WBC counts were found among the women with IAI alone, MIAC alone, and without MIAC and IAI. CONCLUSION: The women with both MIAC and IAI had a higher maternal WBC count at the time of hospital admission than the remaining women with PPROM. The maternal WBC count at the time of admission showed poor diagnostic indices for the identification of the presence of both MIAC and IAI. Maternal WBC count at the time of admission cannot serve as a non-invasive screening tool for identifying these complications in women with PPROM.
Keywords: Leukocyte Count; dospělí; těhotenství; plodová voda; Humans; lidé středního věku; Middle Aged; mladý dospělý; Fetal Membranes, Premature Rupture; Chorioamnionitis; Adult; počet leukocytů; Adolescent; ženské pohlaví; Amniotic Fluid; lidé; chorioamnionitida; mladiství; předčasný odtok plodové vody; Pregnancy; Young Adult; Female